Archiving of Clippings - Anameriç, Hakan (Information World, 2014)
Newspapers and magazines/journals are widely used media that inform people on current social, cultural, political, and economical events. Although newspapers and magazines/journals are not long lasting since the last quarter of the XVIIIth century, because of their nature they are considered as collection and archival materials by some researchers and interested people. However, those people and researchers collect only clippings that are interested and can be utilizied instead of keeping the whole of the newspapers and journals. Interested sections that are cut from the journals and newspapers are named clippings Compared with other archival materials handling and archiving clippings need special care. In this study how newspaper/ journals clippings are identified, cataloged, archived and preserved is described with relevant examples.